The Simulation Of Drop-Weight Impact Test On Ramie-Eglass Hybrid Fiber Composite For Jaloe Kayoh Wall Material - Tamlicha, akram; Rizal, Samsul; Hasanuddin, Iskandar; Noor, Muhamad Mat; Ikramullah, Ikramullah; Nazaruddin, Nazaruddin (Politeknik Negeri Lhokseumawe, 2024)
The purpose of this study is to simulate drop-weight impact tests on hybrid fibre composites made of ramie and Eglass, which are used to make the traditional Acehnese boat wall material for jaloe kayoh. Using composites of ramie-Eglass fiber hybrid in the construction of jaloe kayoh wall material will significantly enhance the strength, durability, and sustainability of traditional Acehnese boats. The simulation was carried out using the finite element method approach using the Abaqus software. Three distinct laminate layer configurations—three layers (GRG), five layers (GRGRG), and six layers (GRGGRG)—with alternating Eglass and ramie fibres make up the test specimens. The ends of the specimen are set with fixed support to ensure boundary conditions, which limit all active structural degrees of freedom on all sides of the specimen. According to simulation results, the specimen with six laminate layers, measuring 12.498 mm, had the largest displacement. The specimen with six laminate layers has the highest stress concentration, measured at 560.6 MPa, while the specimen with three layers has the highest strain concentration, measured at 0.023. Its indicating that the lamina variation can influence the structural performance of the jaloe kayoh material. This research contributes to understanding the potential of ramie-Eglass hybrid fiber composites to enhance the safety and durability of traditional vessels such as jaloe kayoh. The implications of the results can serve as a foundation for the development of superior structural materials in the future.